A highly selective and reversible water-soluble polymer based-colorimetric chemosensor for rapid detection of Cu2+ in pure aqueous solution. (10th March 2016) - Li, Guang; Tao, Farong; Liu, Qian; Wang, Liping; Wei, Zhuang; Zhu, Fen; Chen, Wenxiu; Sun, Houyu; Zhou, Yujie
Abstract : A novel reversible colorimetric chemosensor based on polyethylene glycol has been developed to detect Cu 2+ ions in pure aqueous solution. Abstract : A novel reversible colorimetric chemosensor, PEGRh, based on polyethylene glycol bearing a rhodamine unit has been successfully developed. PEGRh exhibited high selectivity and sensitivity towards Cu 2+ with a short response time in pure aqueous solution, and the results could be monitored directly by the naked eye. The detection limit was as low as 2.5 × 10 −8 M. PEGRh could detect Cu 2+ over a wide pH range of 4–10. In addition, PEGRh is also a reversible colorimetric chemosensor, and it could be made into a test paper to conveniently detect Cu 2+ in real water samples.